KELEMBAGAAN KELUARGA BERENCANA DAERAH: STUDI KASUS PENATAAN LEMBAGA KELUARGA BERENCANA DI KOTA YOGYAKARTA - , KHOIRUL SHOLEH ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Strengthening institutional become one of the objectives of revitalization in family planning (KB) programs that experiencing decline since autonomy era. For that, by law No. 52 of 2009, the provincial and regency/city were instructed to form the Regional Population and Family Planning Board ( BKKBD ). Institution in charge of facilitating the formation BKKBD is representative BKKBN of each province . For BKKBN Representatives of DIY, BKKBD more likely formed in Yogyakarta City because the implementations KB handled its own institutions, apart from other government affairs. However, based on various considerations made by Yogyakarta City Government , the agency will be established to deal with matters of family planning in the city of Yogyakarta not BKKBD but Agency for Community Empowerment, Women, Child Protection and Family Planning (BMPPPA and KB). Based on the case, this study aims to find out why the Yogyakarta City Governmet did not establish the BKKBD as mandated by law No.52 of 2009 but chose to form BPMPPA and KB. The research is a qualitative case study methode. From the research, it is concluded why The Yogyakarta City Government will not establish BKKBD. First , The Yogyakarta City Government assesed KB and population affairs can be carried out without having to form BKKBD. Second , in terms of budget, human resources , common tasks and functions , and institutional adjustment, BPMPPA and KB considered more as needed than BKKBD. Third, the government's policy of Yogyakarta City in the formation of local organizations are not always in line with the center government . That is , the question of BKKBD not the first case in the city of Yogyakarta . However, the problem is not issues at local only. At the center of governement, BKKBN and Ministry of Internal Affairs that should encourage the establishment of BKKBD not doing earnstly. BKKBN Representatives of DIY also have difficulity forming BKKBD in their area. That is due some problems, lack of authority, assessment that comitment of local governments is more important than isntitutions, and fear of existence representatives of the provincial BKKBN if BKKBD formed